Literatur Review: Efektifitas Metode Moist Wound Healing Dan Metode Konvensional Terhadap Penyembuhan Ulkus Diabetikum - Yeni, Neng; Astuti, Esthi; Nurlaela , Marisah; Rachmawati, Annisa Ena; Sartika, Imas; Suryaniaga, Suryaniaga (Pustaka Galeri Mandiri, 2025)
Diabetes mellitus is a chronic metabolic disease with an increasing incidence rate, and one of its most frequent complications is diabetic ulcers, which significantly impact morbidity, mortality, and amputation risk. Wound care plays a crucial role in managing diabetic ulcers, with the Moist Wound Healing (MWH) method and conventional methods still widely applied. This literature review aims to examine the comparative effectiveness of MWH and conventional methods in diabetic ulcer healing. Article searches were conducted through PubMed, ScienceDirect, and Google Scholar databases with a publication range of 2015–2025. From 51 identified articles, 10 studies met the inclusion criteria and were analyzed using a narrative synthesis approach. The findings indicate that MWH is more effective than conventional methods in accelerating diabetic ulcer healing, as evidenced by increased granulation tissue formation, faster epithelialization, reduced exudate, and decreased risk of infection and pain. Although the initial cost of modern dressings is relatively higher, MWH is more economical overall due to shorter healing duration and reduced length of care. In conclusion, MWH has been proven superior to conventional methods and can be recommended as the standard approach for diabetic ulcer wound care, while still considering patient clinical conditions, dressing availability, and healthcare resources